High-quality single-crystal thulium iron garnet films with perpendicular magnetic anisotropy by off-axis sputtering - C. N. Wu (AIP Advances, 2018)
High-quality single-crystal thulium iron garnet (TmIG) films of 10-30 nm thick were grown by off-axis sputtering at room temperature (RT) followed by post-annealing. X-ray photoelectron spectroscopy (XPS) was employed to determine the TmIG film composition to optimize the growth conditions, along with the aid of x-ray diffraction (XRD) structural analysis and atomic force microscope (AFM) for surface morphology. The optimized films exhibited perpendicular magnetic anisotropy (PMA) and the saturation magnetization at RT was ∼99 emu/cm3, close to the RT bulk value ∼110 emu/cm3 with a very low coercive field of ∼2.4 Oe. We extracted the H⊥ of 1734 Oe and the peak-to-peak linewidth ΔH of ferromagnetic resonance are only about 99 Oe, significantly lower than that of PLD grown TmIG film and bulk single crystals. The high-quality sputtered single-crystal TmIG films show great potential to be integrated with topological insulators or heavy metals with strong spin-orbit coupling for spintronic applications.